2018
DOI: 10.1101/351544
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Retrospective cues mitigate information loss in human cortex during working memory storage

Abstract: Working memory (WM) enables the flexible representation of information over short intervals. It is well-established that WM performance can be enhanced by a retrospective cue presented during storage, yet the neural mechanisms responsible for this benefit are unclear. Here, we tested several explanations for retro-cue benefits by quantifying changes in spatial WM representations reconstructed from alpha-band (8-12 Hz) EEG activity recorded from human participants (both sexes) before and after presentation of a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 51 publications
3
9
0
Order By: Relevance
“…In keeping with earlier studies (e.g., Sprague et al, 2016;Wolff et al, 2017), Ester et al (2018) interpreted the partial recovery of location-specific information observed during valid late trials as evidence that participants were able to supplement active memory representations indexed by alpha-band activity with other information sources not indexed by this activity, including but not limited to "activity silent" WM or long-term memory. In this study, we asked whether participants' ability to exploit these additional memory stores is time-dependent.…”
supporting
confidence: 77%
See 2 more Smart Citations
“…In keeping with earlier studies (e.g., Sprague et al, 2016;Wolff et al, 2017), Ester et al (2018) interpreted the partial recovery of location-specific information observed during valid late trials as evidence that participants were able to supplement active memory representations indexed by alpha-band activity with other information sources not indexed by this activity, including but not limited to "activity silent" WM or long-term memory. In this study, we asked whether participants' ability to exploit these additional memory stores is time-dependent.…”
supporting
confidence: 77%
“…If so, then one would expect that the extent of retrocue-driven recovery in estimates of location information would decrease as the temporal interval separating the encoding display and retrocue increases. We tested this possibility by replicating the neutral and VL conditions from Ester et al (2018) while varying the timing of the retrocue between 1.0, 1.5, and 2.0 sec after the encoding display As expected, we found that degree of information recovery was linearly and inversely related to the interval separating the retrocue and the encoding display, suggesting that representations stored in "offline" memory systems degrade or become more difficult to access over time.…”
mentioning
confidence: 78%
See 1 more Smart Citation
“…Following earlier work (e.g., Foster et al, 2016;Samaha et al, 2016;Ester et al, 2018;Nouri & Ester, 2019), we used spatiotemporal patterns of induced alpha-band (8-12 Hz) activity over occipitoparietal electrode sites to track the contents of spatial working memory during the recall and DMC tasks. Specifically, we modeled sample-by-sample estimates of alpha band activity recorded during the spatial recall task as a combination of 12 location filters, each with an idealized tuning curve (a cosine raised to the 12 th power).…”
Section: Experiments 3 -Eegmentioning
confidence: 99%
“…Experiment 3 relied on a fundamentally different signal than Experiment 2 (induced-alpha-band activity vs. evoked 30 Hz power, respectively). Following earlier research(Kok et al, 2017;Ester et al, 2018;Nouri & Ester, 2019), we used a variant of the IEM approach described in Experiment 2 to compute location channel responses. We first isolated alpha-band activity, by bandpass filtering the raw EEG time series at each electrode from 8-12 Hz (zero-phase forward and reverse filters as implemented by EEGLAB's "eegfilt"…”
mentioning
confidence: 99%